Basilisk (Cockatrice) and its Symbolism in the General and South Slavic Context - Bašić (Serbia), Ivana; Uzelac (Serbia), Aleksandar (Bulletin of the Institute of Ethnography SASA; Vol 66 No 1 (2018): Historical Retrospectives of Ethnology and Anthropology, 2018)
The paper deals with the genesis of the image and the symbolism of one of the most striking figures in the imagined medieval bestiary - basilisk, and its related mythical animals - cockatrice, serpent's king, abraxas, both in the general and South Slavic context. An analysis of written sources, from antiquity to medieval and early modern epoch, the folk tradition, as well as artistic representations, show that basilisk and its related forms, emerged through joining the elements of the snake / dragon and the cock / bird. Although essentially ambivalent, they had essentially positive symbolism by representing the driving force and activity, the overcoming of opposites, the establishment of integrity, and the complexity of human nature and cosmic synthesis. Key words: basilisk, cockatrice, snake emperor, Abraxas, imaginary bestiary